Analysis Of Income And Welfare Levels Of Nutmeg Farmers' Households In Negeri Saleman, West Seram Utara District, Central Maluku Regency - Ince Aprilya Farah Azhari; Jeter Donald Siwalette; Noviar Flasiana Wenno (Cita konsultindo, 2024)
The purpose of this study was to determine the income of nutmeg farmers and to determine the level of household welfare of nutmeg farmers in Negeri Saleman, West North Seram District, Central Maluku Regency. This research was conducted in Negeri Saleman, West North Seram District, Central Maluku Regency in February 2024. The sampling method in this study used purposive sampling method, namely 45 respondents randomly selected. The data analysis method used in this research is quantitative method using income and welfare formulas. The results showed that the income of nutmeg farmers in Negeri Saleman, West North Seram District, Central Maluku Regency was quite high with an average income of 45 respondents in one harvest of Rp 57,667,089 and the welfare level of nutmeg farmers in Negeri Saleman, West North Seram District, Central Maluku Regency as many as 32 people in the prosperous category and 13 people in the category of not prosperous.